Vescimonas gen. nov., Vescimonas coprocola sp. nov., Vescimonas fastidiosa sp. nov., Pusillimonas gen. nov. and Pusillimonas faecalis sp. nov. isolated from human faeces. Issue 11 (2nd November 2021) - Kitahara, Maki; Shigeno, Yuko; Shime, Mari; Matsumoto, Yuki; Nakamura, Shota; Motooka, Daisuke; Fukuoka, Shota; Nishikawa, Hiroyoshi; Benno, Yoshimi
Abstract : Six strains of Gram-stain-negative, obligately anaerobic, non-spore-forming, non-motile rods were isolated from human faeces. Based on phylogenetic characteristics, the six isolates were included in the family Ruminococcaceae, and divided into three groups. The six isolates showed 16S rRNA gene sequence similarity values lower than 96.2 % to the closely related species, Oscillibacter ruminantium GH1 T, Oscillibacter valericigenes Sjm18-20 T and Dysosmobacter welbiomis J115 T . Coherently with the 16S rRNA gene sequence results, the in silico DNA–DNA hybridization and average nucleotide identity values clearly indicated that strains MM35 T, MM50 T and MM59 T belong to different species from the closely related three species. Based on phenotypic features and phylogenetic positions, three novel species, Vescimonas coprocola gen. nov., sp. nov., Vescimonas fastidiosa gen. nov., sp. nov. and Pusillimonas faecalis gen. nov., sp. nov. are proposed. The type strain of V. coprocola is strain MM50 T (=JCM 34012 T =DSM 111893 T ). The type strain of V. fastidiosa is strain MM35 T (=JCM 34016 T =DSM 111899 T ). The type strain of P. faecalis is strain MM59 T (=JCM 34011 T =DSM 111669 T ). The DNA G+C contents estimated according to the whole genomes of strains MM35 T, MM50 T and MM59 T were 56.4, 58.2 and 55.2 mol%, respectively.